2016
DOI: 10.1111/gcbb.12363
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons and volatile organic compounds in biochar and biochar‐amended soil: a review

Abstract: Residual pollutants including polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), and carbon (aceous) nanoparticles are inevitably generated during the pyrolysis of waste biomass and remain on the solid coproduct called biochar. Such pollutants could have adverse effects on the plant growth as well as microbial community in soil. Although biochar has been proposed as a ‘carbon negative strategy’ to mitigate the greenhouse gas emissions, the impacts of its application with respect to lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(66 citation statements)
references
References 126 publications
(285 reference statements)
3
61
1
1
Order By: Relevance
“…Additionally, pathways involved in the metabolism of aromatic compounds were significantly higher in biochar-amended samples, including pathways for the degradation of some naturally occurring aromatics from plants and polycyclic aromatic hydrocarbons (PAHs), likely associated with the biochar (68). This finding contrasts with previous studies that observed decreased degradation of PAHs in biochar-amended soils due to limited bioavailability, such as PAH adsorption onto the biochar surface (69,70). Interestingly, control samples were enriched in the pathways involved in the degradation of lignin precursors, (i.e., cinnamic acid) (71) and several ring-cleaving enzymes within the 4-hydroxyphenylacetic acid catabolism pathway (72).…”
Section: Discussioncontrasting
confidence: 78%
“…Additionally, pathways involved in the metabolism of aromatic compounds were significantly higher in biochar-amended samples, including pathways for the degradation of some naturally occurring aromatics from plants and polycyclic aromatic hydrocarbons (PAHs), likely associated with the biochar (68). This finding contrasts with previous studies that observed decreased degradation of PAHs in biochar-amended soils due to limited bioavailability, such as PAH adsorption onto the biochar surface (69,70). Interestingly, control samples were enriched in the pathways involved in the degradation of lignin precursors, (i.e., cinnamic acid) (71) and several ring-cleaving enzymes within the 4-hydroxyphenylacetic acid catabolism pathway (72).…”
Section: Discussioncontrasting
confidence: 78%
“…It constitutes a significant fraction of OC and has received considerable attention due to its physical and chemical properties being remarkably different from those of other fractions of OC. As a result, the roles of BC differ from those of OC in a wide range of biogeochemical processes, such as the regional/global carbon cycle (Bird et al, 2015;Guo et al, 2004;Sánchez-García et al, 2012), climate change (Menon et al, 2002;Ramanathan & Carmichael, 2008), sorption of toxic pollutants, and bioavailability/fate (Dutta et al, 2017). It is therefore of great necessity to calculate and compare OC and BC fluxes independently and to determine the factors that regulate these fluxes in coastal regimes accurately.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that soils amended with exogenous organic matter increase pollutant sorption and reduce their availability. Many different amendments have been dedicated for this purpose (Koltowski et al 2016;Kuśmierz et al 2016;Dutta et al 2017;Ćwieląg-Piasecka et al 2018;Bejger et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, various researchers propose the application of ERCM to immobilize PAHs in soils (Beesley et al 2011;Ghosh et al 2011;Koltowski et al 2016;Kuśmierz et al 2016;Dutta et al 2017). These sorbents mainly reduce the freely dissolved fraction of the contaminants that reach the pore water by diffusion, sorption, and partitioning processes (Pignatello 2012;Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%